Contemplating a Return to the Depths - Hutchison, Andrew (2016)
This chapter describes the process that led to the inception of the 2015 mission to the wrecks of HMAS Sydney and HSK Kormoran, the gathering of the stakeholder groups, and the research process to prepare for the mission.